1998
DOI: 10.1152/ajpcell.1998.275.4.c1058
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB inactivation converts a hepatocyte cell line TNF-α response from proliferation to apoptosis

Abstract: Toxins convert the hepatocellular response to tumor necrosis factor-α (TNF-α) stimulation from proliferation to cell death, suggesting that hepatotoxins somehow sensitize hepatocytes to TNF-α toxicity. Because nuclear factor-κB (NF-κB) activation confers resistance to TNF-α cytotoxicity in nonhepatic cells, the possibility that toxin-induced sensitization to TNF-α killing results from inhibition of NF-κB-dependent gene expression was examined in the RALA rat hepatocyte cell line sensitized to TNF-α cytotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
214
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 174 publications
(237 citation statements)
references
References 33 publications
(55 reference statements)
18
214
5
Order By: Relevance
“…The phenotype and altered gene induction for cyclin D1 and Bcl-xL observed in HFD-fed mice may have been the result of disturbances in the regulatory mechanisms that affect cellular proliferation and survival, in which TNF-␣-regulated NF-B is essential. [10][11][12][13][14][15] Supershift EMSA experiments showed that both p50/p65 heterodimers and p50 homodimers of NF-B were present in livers from control as well as HFD-fed mice (unpublished data). In both groups, an early peak of NF-B DNA-binding activity was seen 30 minutes to 1 hour after PHx (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenotype and altered gene induction for cyclin D1 and Bcl-xL observed in HFD-fed mice may have been the result of disturbances in the regulatory mechanisms that affect cellular proliferation and survival, in which TNF-␣-regulated NF-B is essential. [10][11][12][13][14][15] Supershift EMSA experiments showed that both p50/p65 heterodimers and p50 homodimers of NF-B were present in livers from control as well as HFD-fed mice (unpublished data). In both groups, an early peak of NF-B DNA-binding activity was seen 30 minutes to 1 hour after PHx (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…34 The activation of TNF-␣ as a consequence of LPS stimulation may contribute to the higher levels of apoptosis seen in steatotic livers. 14,35 Moreover, it has been shown that due to increased adiposity, mice fed an HFD have elevated levels of leptin, 36 which, besides the regulation of food intake, also has immunomodulatory functions. 37 In particular, leptin augments inflammation through an increased release of cytokines, such as TNF-␣, which is released in large quantities from tissue macrophages, including Kupffer cells in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[␥-32 P]ATP was from NEN Life Science Products (Boston, MA). Adenovirus expressing the mutant I B (Ad5I B) and control adenovirus Ad5LacZ were provided as previously reported (9). Due to missense mutations at phosphorylation sites where serines 32 and 36 are replaced with alanines, the mutant I B irreversibly binds to NF-B, preventing its activation (9).…”
Section: Methodsmentioning
confidence: 99%
“…Gels are representative of three independent experiments from three diVerent isolations; ExCO 100-fold excess cold NF B oligonucleotide; -AB EMSA without NF B p65 supershift antibody Discussion NF B is an essential component of ionizing radiation-triggered signal transduction pathways that can lead either to cell death or survival, depending on the respective cell type (for a review see [17]), and numerous studies have demonstrated that inhibition of NF B by diVerent means increased sensitivity of cancer cells to the apoptotic action of diverse eVectors such as TNF-, chemo-or radiotherapies (for review see [18]). In both primary rat hepatocytes and a non-transformed rat hepatocyte cell line, inhibition of NF B-activity by adenoviral delivery of a I B superrepressor sensitized these cells to death from TNF- [19,20]. However, TNF-was also recently shown to sensitize for DNA-damage-induced apoptosis via an NF-kappa-B independent mechanism [21].…”
Section: Evect Of I B-antisense On Susceptibility Of Irradiated Hepatmentioning
confidence: 99%